If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + 2x = 90 Solving 15 + 2x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 2x = 90 + -15 Combine like terms: 15 + -15 = 0 0 + 2x = 90 + -15 2x = 90 + -15 Combine like terms: 90 + -15 = 75 2x = 75 Divide each side by '2'. x = 37.5 Simplifying x = 37.5
| -2x-93=11x+154 | | 2(k-1)=34(-k-2) | | -3(-2x+4)+-2(x-5)= | | 5(2x-4)-3(2x+1)=12 | | 4.2+1.8(2x+3)=45.6 | | (4x-5)^2=(3x+2)(8x-10) | | 3t^2+9t+3=0 | | 2/3=-1s/3 | | 2a+7/4a^2+1 | | 7x+9=100 | | 2(a-4)=49-(29+4) | | N(3+2)+6=5n+(10-3) | | 4x^2-24x-2 | | -8(2a-3b)-5(6b-4a) | | 4y+7=51 | | 1/4(x+2)=8 | | 6times9 | | x-12÷6=9= | | 2x+x-1+2x+2x-3+x=76 | | 3+1(y-4)=2(1-y) | | (3x+5)=5x=2 | | 6x-4=4x+10 | | (n+18)squared=576 | | 8x-3-4x=9+4x-12 | | 67-5x=4x+17 | | -9+-3= | | .34x+1.6=.425(x+5)-.2 | | 6x+3-4x=4x+5 | | 50/x=10 | | 3x-x=30-12 | | 6-(3x-4)=-x-6 | | 108-3x=3x |